PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Dyah Meisaroh; Siti Halidjah; Sugiyono Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research is to know the influence of the application of scramble type of cooperative learning model in thematic learning on the learning outcomes tin fifth grade V students of Elementary  School 39 Pontianak Kota. The method used is experimental method, with the form of Nonequivalent Control Group Design. The population in this study is amounted to 63 students. The sample is using the Non-probability sampling technique with purpossive sampling which amounted to 63 students. Data collection techniques used are measurement techniques with using the tool in the form of test with multiple choice form amounted to 50 problem. The result of the research is the averagee  post-test control class is 71,96 meanwhile averagee post-test experiment class is 76,25. Based on the analysis of hypothesis using t-test obtained tcount = 2,179 for dk = 56 and α = 5% obtained ttable = 1,6788 means tcount (2,179) > ttable (1,6788), then Ha accepted. From the calculation of effect size obtained is 0,41 (medium category). It means the learning with the aplication of scramble type of cooperative learning model has a positive influence on the learning outcomes tin fifth grade V students of Elementary  School 39 Pontianak Kota.    Keywords: Influence, Learning Outcomes, Scramble Model.